Lipaemic and glycaemic excursion : differences while sitting and standing after meal - Teo, Jieming (2016)
Diseases contracted due to poor cardiometabolic health, including ischaemic heart disease, stroke and diabetes mellitus, were among the ten leading causes of death globally. Postprandial excursions of plasma triglyceride and glucose concentrations were found to be predictors of cardiometabolic diseases. Prolonged sitting has shown to be an independent risk factor associated with such diseases. This study tested the hypothesis that prolonged post- meal accumulated standing leads to lower rise in postprandial plasma triglyceride and glucose concentrations relative to post-meal sitting. 5 male subjects (Age: 24 to 27y, BMI: 22.0 (2.6)kg/m2, body fat percentage: 16.46 (8.45)%) rested in one trial and stood for 270 minutes accumulatively over 6 hours in another trial, with both trials occurring at least 1 week apart. 2 test meals were provided in each trial. Analysis of blood samples did not show that standing led to attenuation of postprandial lipaemia. For postprandial glycaemia, absolute postprandial hourly means at 1h and 6h were significantly higher in sitting than standing trials by 15.2% and 28.5% respectively. The peak plasma glucose concentration for sitting trial was 22.9% higher than that of standing trial. Overall hourly change in plasma glucose concentrations were found to be significantly greater in sitting than standing trial, P = .021. AUC and iAUC of glucose-time graph of sitting trial is 9.8% and 221.1% higher than that of standing trial respectively, P < .05. These results show that post-meal standing could lead to healthier cardiometabolic marker profile. Future research could provide typically-consumed meals to better test the hypothesis.